Sovereignty and Food Politics in East Timor - Kammen, Douglas (Kasarinlan: Philippine Journal of Third World Studies; Vol 26 No 1-2 (2011): Food Sovereignty in Southeast Asia)
With the outbreak of the 2006 crisis, food security became intertwined with peacekeeping and the political struggle over state power in East Timor. Today, efforts to address food security have been hijacked by the political interests of the current government and the private interests of those in power. This article provides a brief historical overview of food (in)security in East Timor and then outlines the development of national agricultural and food security policy, arguing that in the face of weak state capacity, rice imports have come to serve the political and private interests of the current government.
Keywords: East Timor, rice imports, food insecurity, state capacity, political elites